Web and Application Program Interface (API) Design “Parmon” Modern Parking Application - Aco Wahyudi; Eko Junirianto; Annafi Franz (TEPIAN, 2021)
Samarinda city is one of the cities with large local revenue potential in the large parking fee sector. This is evidenced by the quite fast increasing number of users of two-wheeled and four-wheeled vehicles. But due to the increase in vehicle users in Samarinda it has not had a significant impact on the parking fee sector. This is because there is no clear record of every parking transaction. In this case the parking lot is open or roadside. The collection of parking fees in Samarinda there are still many obstacles faced by UTPD parking management, there are still many illegal parking spaces managed by irresponsible elements. One technology that is currently quite developed is the web. With the web, all data and information can be distributed effectively and efficiently and contain and display various information that can be accessed by various devices. Based on the problems and technological developments that have been presented, an idea emerged about the need to create a web-based information system to store and record transactions at any time and create an API for supporting applications. It is expected from this study that every transaction for drivers and drivers can be recorded so that the government can clearly know the income and the amount of levy tax from parking that must be paid by each parking attendant in the “Parmon” application.